THE RELATIONSHIP BETWEEN LEARNING MOTIVATION AND SELF-EFFICACY THROUGH SCIENCE LEARNING IN ELEMENTARY STUDENTS - Agustini, Ella Yuliarti; Tarihoran, Naf'an; Sapriati, Amalia (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
Motivation is needed in learning activities. Motivated students are easier to develop thinking skills so that the learning outcomes achieved are better. Learning motivation is also needed to improve science learning outcomes which are not just memorizing a number of facts, for that we need an encouragement from oneself and others to make a comprehensive attitude change that is integrated through knowledge and skills. The achievement of success and success does not only require strong motivation in learning, but also other factors such as self-efficacy or self-confidence in completing school assignments. Students who have high self-efficacy have high learning motivation. This study aims to analyze the relationship between learning motivation and self-efficacy, together with the science learning outcomes of fourth grade elementary school students in Pandeglang District. The study was conducted on 275 fourth grade students in the Pandeglang District, namely SDN Pandeglang 1, SDN Pandeglang 3, SDN Pandeglang 4, and SDN Pandeglang 6. The instrument used to measure motivation and self-efficacy was in the form of a questionnaire with four alternative answer options, while to measure motivation and self-efficacy was in the form of a questionnaire with four alternative answer options. Science learning outcomes used multiple choice test questions with four answer options. Hypothesis testing is done by using multiple regression test. The results of the study concluded that: 1) There was a positive relationship between learning motivation and students' science learning outcomes; 2) There is a positive relationship between self-efficacy and students' science learning outcomes.; 3) There is a positive relationship between learning motivation and self-efficacy, together with students' science learning outcomes.